Tuberculous intestinal perforation in a case of Burkitt lymphoma on chemotherapy - A case report - Kekre, Geeta; Gupta, Rahul; Gupta, Abhaya; Kothari, Paras; Patil, Prashant; Dikshit, Vishesh; Kamble, Ravi (Indian Journal of Case Reports, 2015)
Intestinal perforation induced by chemotherapy in a patient of Burkitt lymphoma is a known potential complication whichcarries high mortality. Perforation may also occur as a result of the transmural nature of the tumour. Patients on chemotherapy are prone to contract infectious diseases due to a compromised immune system. Pulmonary tuberculosis has been reported in these patients, but abdominal tuberculosis has not. We report the case of a five year old boy on chemotherapy for Burkitt lymphoma, and who developed a tuberculous jejunal perforation. The patient underwent drain insertion and stabilization followed by exploratory laparotomy with resection of the pathological segment and closure of the duodenal stump at the fourth part. Bowel continuity was re-established by gastrojejunostomy. Histopathologic examination of the resected segment revealed intestinal tuberculosis. Anti -tubercular therapy was started and continued for nine months. The last cycle of chemotherapy was administered 1 month after surgery. At 1 year of follow up the patient is asymptomatic and thriving well.